Analyzing the microstructure and mechanical properties in LM6 aluminium casting in sand casting process. (2022) - Kandpal, Bhaskar Chandra; Johri, Nitin; Bhatia, Pramod; Masih, Chris; Kumar, Karan
Abstract: Casting defects is the one and only barrier in the casting process. The sand casting process also faces the same problem. Finding out the most accurate and definite condition to attain the best casted or manufactured product is the difficult task for every industry. To avoid the loss of strength in any product, most of the industries in present time use trial and error method. But due to various hurdles like time lacking, expensive material cost causes higher than expected cost to the industries. In this paper, an effort is made to reduce the casting defects in sand casting of LM6 aluminium alloy by performing correct procedure in casting process. It was observed that the casting defects can be reduced by using the specific good quality sand with various parameters like binder percentage (%), moisture content, additives and pouring temperature (℃). When the optimum test were conducted for sand, it was found that the binder percentage (which in case for black sand and yellow sand) in the moulding sand was very high and the size of sand particles was coarse. The higher percentage of binder causes defects like shrinkage, irregular shape, hot tear and many more. At industry level it is very important to improve the quality of sand and to achieve zero-defect product, the following practices should work on so that the casting defects can easily be reduced successfully. This paper mainly focuses on casting defects and their remedies.